Precursors to modernization theory in United States government policy: a study of the Tennessee Valley Authority, Japanese occupation, and Point Four Program - Aksamit, Daniel Victor (Kansas State University, 2009)
In the 1960s, modernization theory became an important analytical tool to conceptualize change in the Third World. As opposed to rebuilding societies that had already attained industrialization as was done with the Marshall Plan, modernization theorists focused on creating a total theory that encapsulated the entire arc of development from a traditional agricultural society to a modern industrial society. Aware that a colonial relationship subordinating nations on the periphery to the West was impossible, modernization theorists sought to create an amicable bond based on consent. Modernization theory served as the underlying logic of the Alliance for Progress, Peace Corps, and the Strategic Hamlet Program in Vietnam. This thesis argues that although modernization theory certainly had novel aspects, notably its social and psychological elements, much of the theory simply consisted of the coalesced logic, assumptions, and methods acquired from three previous American experiences with development, particularly the Tennessee Valley Authority (TVA), Point Four Program, and occupation of Japan after World War II. I argue that thought concerning development from the 1930s through the 1960s should be seen as a continuum rather than view modernization theory in the 1950s and 1960s as completely novel. Modernization theorists both intentionally and unknowingly incorporated into modernization theory the logic, assumptions, and methods developed in previous development schemes. Chapter Two examines how the democratic decentralized structure of the TVA became embedded in post-World War II thought about development as an alternative to communist models of development. The chapter also explores TVA director David Lilienthal’s and modernization theorists’ emphasis on technology as both harbingers of modernization and evidence of modernity. Chapter Three investigates how Chester Bowles, the director of the Point Four Program in India, and modernization theorists used Keynesian economics in their development model, arguing that modernization could be induced by government spending in agriculture, education, infrastructure, and health and sanitation. Chapter Three also explores how Bowles and modernization theorists used an evolutionary theory of development derived from America’s past to guide their development in the Third World. Chapter Four examines the similarity between what officials of the Japanese occupation and modernization theorists considered traditional and modern. The chapter also explains that both groups believed in the universal applicability of the principles of American society.
Keywords: Modernization theory; Third world development; Tennessee valley authority; Japanese occupation; Point four program; Walt rostow; History, United States (0337)